How authoritarian regimes counter international sanctions pressure - Christian von Soest (German Institute of Global and Area Studies (GIGA), 2023)
Based on current literature, this paper analyses the nature and effects of external pressure imposed on authoritarian regimes. Around three-quarters of all countries under United Nations, United States, and European Union sanctions are authoritarian, and 'democracy sanctions' that aim at improving democratic and human rights in targeted countries constitute the biggest sanctions category. Yet, authoritarian regimes represent particularly problematic targets as they can more easily shield themselves from external pressure than their democratic counterparts can. Authoritarians have a tighter grip on the public discourse and the struggle over the meaning of sanctions. They often even use them to their own advantage, denouncing sanction senders as 'imperialist' and blaming them for their economic woes. The paper presents trends in the application of sanctions pressure against authoritarian regimes, reviews mechanisms of how economic and diplomatic restrictions work, and examines authoritarian targets' attempts to engage in pressure proofing.
Keywords: 300; Authoritarian regimes; external pressure; sanctions; rally-round-the-flag effect; pressure proofing